The Effect of Humanistic Leadership and Employee Engagement on Civil Servant Performance in the Pesawaran Regency Government: The Mediating Role of Psychological Safety and the Moderating Role of Tenure - Andini; Febrianty; Reza Hardian Pratama (Yayasan Multidimensi Kreatif, 2026)
This study aims to analyze the influence of humanist leadership and employee engagement on the performance of State Civil Apparatus (ASN) employees in the Pesawaran Regency Government, with psychological safety as a mediating variable and working period as a moderation variable. The study used a quantitative approach through the distribution of questionnaires and was analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method.The results of the study show that employee engagement has a positive and significant effect on employee performance. Humanist leadership has been proven to increase employee engagement and psychological safety. In addition, psychological safety mediates the influence of humanist leadership on employee performance. Tenure moderates the relationship between employee engagement and employee performance, but does not moderate the influence of humanist leadership on performance. This study concludes that improving the performance of ASN can be achieved through strengthening employee engagement, creating psychological safety, and implementing humanist leadership in public organizations.